ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN KONTRASEPSI PADA WANITA MENIKAH USIA DINI DI KABUPATEN BANGLI - I Ketut Sudibia, Dewa Ayu Dian Yulita Sari, (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Determination of the right contraception is very important for prospective acceptors. Respondents from this study were married women at an early age in Bangli District as many as 120 people as samples. The variables studied in this study were knowledge, information on family planning field officers, perceptions of family planning benefits, husband's support and contraceptive use which were then analyzed using path analysis. The results showed that from the three independent variables in the form of knowledge, information on KB field officers, the perception of family planning benefits had a significant effect on the dependent variable, namely husband's support. Knowledge does not have a significant effect on contraceptive use while information on family planning field workers and perceptions of family planning benefits affect work decisions on contraceptive use, husband support variable is a variable that mediates the influence of knowledge, information on family planning officers, and perceptions of KB benefits on contraceptive use.